2019
DOI: 10.1002/admi.201900042
|View full text |Cite|
|
Sign up to set email alerts
|

Origin of Ferroelectric Phase in Undoped HfO2 Films Deposited by Sputtering

Abstract: the formation of a non-centrosymmetric Pca2 1 orthorhombic phase (o-phase). [1][2][3][4][5][6][7] For increasing doping concentrations, ALD HfO 2 films undergo a phase transition from a non-ferroelectric m-phase to ferroelectric orthorhombic phase and for higher concentrations to the tetragonal phase (t-phase; space group: P4 2 /nmc) if the dopants are smaller than Hf like Si and Al, or to the cubic phase if the dopants are larger than Hf like Gd, La, Sr, and Y. [8] Besides the influence of doping, four other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
151
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 139 publications
(174 citation statements)
references
References 43 publications
(75 reference statements)
15
151
0
2
Order By: Relevance
“…[41] Density functional theory (DFT) calculations also verified this correlation that tetragonal and orthorhombic phase formation is suppressed for higher oxygen concentrations in HfO 2 , and monoclinic phase nuclei are formed. [41,99] In addition, the phonon vibrations upon the application of voltage bias would decrease with the increase in oxygen vacancy concentration. In this sense, the ferroelectric behavior such as fatigue and imprint field would degrade under high oxygen vacancies.…”
Section: Oxygen Dependencymentioning
confidence: 72%
See 1 more Smart Citation
“…[41] Density functional theory (DFT) calculations also verified this correlation that tetragonal and orthorhombic phase formation is suppressed for higher oxygen concentrations in HfO 2 , and monoclinic phase nuclei are formed. [41,99] In addition, the phonon vibrations upon the application of voltage bias would decrease with the increase in oxygen vacancy concentration. In this sense, the ferroelectric behavior such as fatigue and imprint field would degrade under high oxygen vacancies.…”
Section: Oxygen Dependencymentioning
confidence: 72%
“…[45] In addition, the multigrain nature of the polycrystalline hafnia thin films poses another requirement on a "wake-up" process, [56] which is not favorable for ferroelectric memory devices. Other techniques have also been used for the growth of hafnia thin films, such as sputtering, [41,69,70] metal-organic chemical vapor deposition (MOCVD), [71] or chemical solution deposition (CSD), [72] almost all resulting in polycrystalline films.…”
Section: Polymorphism Of Hafnia Thin Filmsmentioning
confidence: 99%
“…[32,33] Similar observations of larger remanent polarizations in films containing greater quantities of oxygen vacancies have been made experimentally, [12,13,34] leading to further development of HfO 2 deposition processes designed to enhance the concentrations of these defects. Such process modifications have included alteration of the oxygen content in the process gas during sputtering [12,13] or duration of the ozone dose during ALD. [34] Aside from HfO 2 processing conditions, studies have observed varied ferroelectric performance dependent upon the selected electrode material.…”
Section: Introductionmentioning
confidence: 74%
“…[18] As PZT and HfO 2 show analogous performance instabilities and the presence of oxygen vacancies in HfO 2 has been widely observed, the current study adopts IrO 2 as an electrode material for HfO 2 -based ferroelectric materials. [11,[19][20][21][22] For pure HfO 2 , the amount of oxygen and oxygen vacancies within the film can significantly influence the stabilization of the crystalline phases. [21,23] It has been shown that oxygen-rich Thin film metal-ferroelectric-metal capacitors with an equal mixture of hafnium oxide and zirconium oxide as the ferroelectric material are fabricated using iridium oxide as the electrode material.…”
mentioning
confidence: 99%
“…[11,[19][20][21][22] For pure HfO 2 , the amount of oxygen and oxygen vacancies within the film can significantly influence the stabilization of the crystalline phases. [21,23] It has been shown that oxygen-rich Thin film metal-ferroelectric-metal capacitors with an equal mixture of hafnium oxide and zirconium oxide as the ferroelectric material are fabricated using iridium oxide as the electrode material. The influence of the oxygen concentration in the electrodes during crystallization anneal on the ferroelectric properties is characterized by electrical, chemical, and structural methods.…”
mentioning
confidence: 99%